Images of the poet’s ego in contradictions of Jarir and Al-Farazdaq - خليل نعمى; عبد الكريم يعقوب; هويدا نجّاري (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study examines the manifestations of the image of the ego in its dialectical relationship with the other, observing the impact of this image on the poetic contents emanating from it through the two themes of lineage and poetic creativity. Language and all its elements, and the basic deep structures that shaped language in some form. The research attempted to reveal the features of the image of the poetic ego and its components, and its various relationships in the contradictions of Jarir and Al-Farazdaq, especially in its relationship with the other/antagonist who does not appear in an independent form in a way that can be diagnosed and discussed, but always appears through the manifestations of the ego in its images. The performance of the image is one of the important methods in poetry, as it is one of its most prominent elements because of the analysis and justification it entails, and the beauty it represents in expression, and the purpose it achieves in the statement, and the ability to influence the recipient. Hence, the research sought to reveal the forms by which the image of the ego was determined, and the mechanism adopted by the two poets in proving the uniqueness and distinction of (the ego), and its impact on the recipients, through the artistic and aesthetic values included in their poetry.